Globalização: a retórica do velho imperialismo - (uma abordagem do imperialismo dos séculos XX/XXI) - Almeida, José Rubens Mascarenhas de (2009)
This work aims to contribute to the study of the current phase of capitalism transnationalization and, within this, the subordinate insertion of the periphery of the system. The approach of the object is done from the systematic rebuilding of both the concept and the historical process, seeking to follow the path of formation and development of the analytical category imperialism, including its sociopolitical dimensions, in a Marxist approach. From a historical perspective, the starting point is the post-World War II (a time of recomposition of capitalism), reaching up to the first decade of the twenty-first century. The focus will prioritarily be on USA/Latin America relations